Systematic Review on the Effects of Food on Mental Health via Gut Microbiome - Simone Lao; Shayna Keying Seow; Rong Ting Ong; Vaidehi S. Dave; Maurice HT Ling (Ital Publication, 2023)
Recent studies have suggested that diet may affect the gut microbiome, subsequently influencing mental health. While several systematic reviews have been done on the effects of diet on mental health via the gut microbiome, there are focused on either specific diets or mental disorders. This systematic review examines the effect of diet and broad-based mental health via the gut microbiome. 21 out of 99 studies published prior to 2023 and listed in PubMed are included. Our analysis suggests that a vegan diet, a Mediterranean-style diet, fiber, probiotics, dietary vitamin D, unpasteurized milk, foods with a low omega-3 to omega-6 ratio, and Xiao Yan Sanmay have positive effects on gut microbiome, leading to a positive influence on mental health, while a meat-rich diet, a high-fat diet, high fructose intake, and zinc deficiency may have negative effects on gut microbiome, leading to a negative influence on mental health. Collectively, the effects of diet on mental health via gut microbiome may be explained by the composition of gut microbiome and the metabolites produced by gut microbiome on gut permeability.   Doi: 10.28991/SciMedJ-2023-05-02-05 Full Text: PDF